Current status and performance evaluation of emerging advanced remediation techniques for the removal of steroidal hormones in water - Martins O. Omorogie (Elsevier, 2024)
Micropollutants such as steroid hormones contaminate water worldwide and cause significant damage. Wastewater treatment plants (WWTPs) partially remove them, and they have low biodegradability leading to their persistence in water bodies. They are endocrine disruptor compounds in aquatic organisms. Various environmental conditions contribute to their persistence in the environment like soil pH, organic matter, soil conditions, and temperature. The aquatic environment is most threatened even when present at very low concentrations. The environment is exposed to steroid hormones from agricultural run-offs, pharmaceutical and industrial waste, and veterinary medicine. Since most WWTPs partially remove contaminants, there is a need for new and improved technologies for higher and more efficient removal of steroid hormones. This paper discusses the fate and toxicity of steroid hormones in the aquatic environment. It further elucidates the existing and emerging technologies in the treatment of steroid hormones in aquatic environments. Finally, the conclusion of this review along with the current limitations and future research perspectives of hormones present in the environment are elucidated.